Manufacturing method of curable film, curable film, laminate, imaging device, semiconductor device, and manufacturing method of laminate
A curable film using silsesquioxane resin addresses substrate warping and cracking in semiconductor devices by forming a uniform, heat-resistant insulating layer that fills irregularities, improving connection reliability.
Patent Information
- Application Number
- JP2023109513
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional semiconductor devices face issues with substrate warping and cracking due to high-temperature treatments, especially when using organic insulating layers, which are sensitive to heat and have limited ability to fill substrate irregularities, leading to poor connection reliability.
A curable film using silsesquioxane resin composition is applied to a support film, dried to form a uniform layer with high heat resistance, and then laminated on substrates with irregularities, providing excellent step-filling performance and reducing warping and cracking.
The method produces a uniform, heat-resistant insulating layer that effectively fills substrate irregularities, enhancing connection reliability and reducing warping, even under high-temperature conditions.
Smart Images

Figure 2025007848000013 
Figure 2025007848000014 
Figure 2025007848000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a curable film, a curable film, a laminate, an imaging device, a semiconductor device, and a method for producing a laminate. [Background technology]
[0002] As semiconductor devices become more sophisticated, they are being made three-dimensional by stacking multiple semiconductor chips. In manufacturing such semiconductor devices with multiple semiconductor chips stacked on top of each other, first, a bonding surface is formed by using a damascene method on the electrode surface of an element or circuit board (hereinafter simply referred to as a substrate) on which two electrodes are formed, in which a bonding electrode made of copper is surrounded by an insulating film. Then, the two substrates are stacked so that the bonding electrodes on the bonding surfaces face each other, and a heat treatment is performed to manufacture the semiconductor device (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-191081 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the manufacturing of the semiconductor device, a high-temperature treatment of 400°C for 4 hours is performed when bonding the electrodes, so the insulating layer used to form the bonding surface is required to have high heat resistance. For this reason, in conventional semiconductor devices, insulating inorganic materials such as SiN and SiO2 are used as the insulating layer. However, insulating layers made of inorganic materials are prone to warping of the substrate, and if the substrate is warped, the connection position of the electrodes may shift or the electrodes may crack when stacked, which may reduce the connection reliability of the semiconductor device. In addition, in recent years, the performance of semiconductor devices has improved, and substrates have become larger and thinner, making substrate warping more likely to occur, and the substrate may crack, especially if it is thin.
[0005] In order to prevent warping and cracking of the substrate due to high-temperature treatment, it is considered to use an organic compound, which has more flexibility than inorganic materials, as an insulating layer. By using an organic compound as an insulating layer, even if the substrate warps, the flexibility can eliminate the warping, and since the insulating layer can be formed by coating, it is expected that productivity will be improved. However, insulating layers made of organic compounds are vulnerable to heat, and outgassing generated by thermal decomposition can easily cause the insulating layer to crack. In response to this, the use of heat-resistant resins as insulating layers is also being considered.
[0006] On the other hand, many substrates of semiconductor devices have a surface with unevenness, since many chips and the like are arranged on the substrate. When a resin composition as a raw material for an organic layer is applied to a substrate having such unevenness to form an organic layer, unevenness of a certain size can be filled, but since the generation of voids due to the shrinkage of the film caused by the evaporation of the solvent is inevitable, there is a problem that there is a limit to filling large unevenness. To solve this problem, it is possible to dry the resin composition in advance to form a film and laminate it on the substrate. However, when the resin composition used in the conventional insulating layer is simply applied on a support film to form a film, there is a problem that the wettability of the resin composition to the release-treated surface of the support film is poor, making it difficult to form a film. In addition, even if a film can be formed, there is also a problem that it is difficult to form a uniform film.
[0007] The present invention aims to provide a method for producing a curable film that can form a uniform film on a support film, and the cured film has excellent heat resistance and excellent step-filling performance even when used on a substrate having large irregularities, a curable film obtained by the method for producing a curable film, a laminate using the curable film, an imaging device and a semiconductor device each having the laminate, and a method for producing the laminate. [Means for solving the problem]
[0008] The present invention includes the following Disclosures 1 to 21. The present invention will be described in detail below. [Disclosure 1] A step of preparing a solution by dissolving a curable resin composition containing a silsesquioxane represented by the following structural formula (1) in a solvent having a boiling point T°C so as to have a viscosity of 700 mPa·s or more and 2000 mPa·s or less; applying the solution onto a release-treated surface of a support film that has been subjected to a release treatment so that the thickness after drying is 50 μm or more; and drying the applied solution at a temperature of T+50° C. or higher for 10 minutes or longer. [ka] In structural formula (1), R 0 , R 1 and R 2 each independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. m and n each represent an integer of 1 or more. [Disclosure 2] The method for producing a curable film according to Disclosure 1, wherein the solution has a solids concentration of 50% by weight or more. [Disclosure 3] The method for producing a curable film according to Disclosure 1 or 2, wherein the boiling point of the solvent is less than 100°C. [Disclosure 4] The method for producing a curable film according to any one of Disclosures 1 to 3, wherein the support film contains polyethylene terephthalate. [Disclosure 5] A curable film having a support film that has been subjected to a release treatment and a resin layer laminated on the release-treated surface of the support film, wherein the resin layer contains a silsesquioxane represented by the following structural formula (1), and the thickness of the resin layer is 50 μm or more. [ka] In structural formula (1), R 0 , R 1 and R 2each independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. m and n each represent an integer of 1 or more. [Disclosure 6] The curable film according to Disclosure 5, wherein the relationship tr>tf is satisfied, where tr is the thickness of the resin layer and tf is the thickness of the support film. [Disclosure 7] 7. The curable film according to Disclosure 5 or 6, wherein the support film is polyethylene terephthalate. [Disclosure 8] The curable film according to any one of Disclosures 5 to 7, wherein the resin layer is heated at 300° C. for 1 hour in the atmosphere and cured, and the cured product has a glass transition temperature of 25° C. or higher and 100° C. or lower. [Disclosure 9] A laminate comprising a substrate having a first surface having projections and recesses and a second surface opposite the first surface, the substrate having an organic layer formed on the first surface and comprising a cured resin layer of the curable film according to any one of Disclosures 5 to 8. [Disclosure 10] 10. The laminate according to Disclosure 9, wherein the height of the projections and recesses of the substrate is 30 μm or more. [Disclosure 11] An imaging device having the laminate according to Disclosure 9 or 10. [Disclosure 12] A semiconductor device having the laminate according to claim 9 or 10. [Disclosure 13] 11. The laminate according to Disclosure 9 or 10, wherein the substrate is a first substrate having a plurality of chips on a first surface thereof. [Disclosure 14] The laminate of Disclosure 13, wherein the organic layer has an inorganic layer on a side of the first substrate that is not laminated. [Disclosure 15] The laminate according to Disclosure 14, having a supporting substrate on a surface of the inorganic layer on which the organic layer is not laminated. [Disclosure 16] The laminate according to any one of Disclosures 13 to 15, further comprising a second substrate on the second surface side of the first substrate, the first substrate and the second substrate being electrically connected to each other. [Disclosure 17] A laminate having an organic layer formed of a cured product of a resin layer of the curable film according to any one of Disclosures 5 to 8, between a third substrate having an electrode and a fourth substrate having an electrode, a laminate in which the electrode of the third substrate and the electrode of the fourth substrate are electrically connected via a through hole penetrating the organic layer. [Disclosure 18] The laminate of Disclosure 17, having an inorganic layer between a third substrate and a fourth substrate. [Disclosure 19] 19. The laminate according to Disclosure 17 or 18, having a barrier metal layer on the surface of the through hole. [Disclosure 20] A process for heating the curable film according to any one of Disclosures 5 to 8 to a temperature equal to or higher than the glass transition temperature of a resin layer, and laminating the resin layer on a first surface of a substrate having a first surface having projections and recesses and a second surface opposite the first surface; and a process for peeling off a support film from the curable film after lamination. and heating the substrate on which the resin layer is laminated to form an organic layer made of a cured product of the resin layer on the substrate. [Disclosure 21] heating the curable film according to any one of Disclosures 5 to 8 to a temperature equal to or higher than the glass transition temperature of a resin layer, and laminating the resin layer onto a surface of a third substrate having an electrode and a fourth substrate having an electrode, the surface having the electrode; peeling the support film from the curable film after lamination; a step of heating the third substrate and the fourth substrate on which the resin layer is laminated to form an organic layer made of a cured product of the resin layer on the third substrate and the fourth substrate; forming a through hole in each of the organic layers; filling each of the through holes with a conductive material; a step of polishing the surfaces of the third substrate and the fourth substrate on the side where the conductive material is filled to form bonding electrodes; A method for manufacturing a laminate, comprising a step of bonding the third substrate and the fourth substrate together so that the bonding electrodes of the third substrate and the fourth substrate are bonded to each other.
[0009] The method for producing a curable film of the present invention first involves preparing a solution by dissolving a curable resin composition containing a silsesquioxane represented by the following structural formula (1) in a solvent having a boiling point T°C so as to have a viscosity of 700 mPa s or more and 3000 mPa s or less.
[0010] [ka] Here, R 0 , R 1 and R 2 each independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. m and n each represent an integer of 1 or more.
[0011] Silsesquioxane has high heat resistance while having the same degree of flexibility as organic compounds, so that by using a cured product containing silsesquioxane as the main component as the insulating layer of a laminate, it is possible to suppress warping and cracking of the substrate and improve the reliability of electrical connection. In addition, when dissolving the curable resin composition containing the silsesquioxane in a solvent, by setting the viscosity of the solution within the above range, it is possible to improve the wettability of the release-treated surface of the support film, and the silsesquioxane can be made into a film.
[0012] In the above structural formula (1), R 0 Each of R independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. 0 R is preferably a phenyl group, an alkyl group having 1 to 20 carbon atoms, or an arylalkyl group, and more preferably a phenyl group. 0 When the alkyl group is a phenyl group, an alkyl group having 1 to 20 carbon atoms, or an arylalkyl group, higher heat resistance can be exhibited.
[0013] In the above structural formula (1), R 1 and R 2Each of R independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. 1 and R 2 R is preferably a phenyl group, an alkyl group or an arylalkyl group having 1 to 20 carbon atoms, and more preferably a phenyl group or a methyl group. 1 and R 2 When the alkyl group is a phenyl group, an alkyl group having 1 to 20 carbon atoms, or an arylalkyl group, higher heat resistance can be exhibited.
[0014] In the structural formula (1), m and n are each an integer of 1 or more and represent the number of repeating units. The m is preferably 30 or more, more preferably 50 or more, and preferably 100 or less. The n is preferably 1 or more, more preferably 3 or more, and preferably 8 or less.
[0015] The weight average molecular weight of the silsesquioxane is not particularly limited, but is preferably 5000 to 150000. When the weight average molecular weight of the silsesquioxane is in the above range, the film-forming property during application is improved, the flattening performance is further improved, and warping and cracking of the element can be further suppressed. The weight average molecular weight of the silsesquioxane is more preferably 10000 or more, even more preferably 30000 or more, more preferably 100000 or less, and even more preferably 70000 or less. The weight-average molecular weight of the silsesquioxane is measured as a polystyrene-equivalent molecular weight by gel permeation chromatography (GPC) using THF as an elution solvent and a Time-MB-M6.0×150 mm (manufactured by Waters Corporation) or an equivalent column, and can be calculated based on polystyrene standards.
[0016] The content of the silsesquioxane is preferably 65% by weight or more and 99% by weight or less in 100% by weight of the curable resin composition. By setting the content of silsesquioxane in the curable resin composition within the above range, it is possible to suppress warping or cracking of the element and further improve the reliability of electrical connection. The content of silsesquioxane in 100% by weight of the curable resin composition is more preferably 70% by weight or more, even more preferably 75% by weight or more, more preferably 98% by weight or less, and even more preferably 97% by weight or less.
[0017] The curable resin composition preferably contains a catalyst. The catalyst has a role of promoting the curing reaction. By including the catalyst in the curable resin composition, the curable resin composition can be cured more completely, and the decomposition of the obtained cured product of the curable film (hereinafter, simply referred to as the cured product) due to high temperature treatment can be further suppressed. Examples of the catalyst include organotin compounds such as dibutyltin dilaurate and stannous acetate, metal carboxylates such as zinc naphthenate, acetylacetonate complexes with zirconium as the central metal, and titanium compounds. Among them, acetylacetonate complexes with zirconium as the central metal are preferred because they can promote the curing of the curable resin composition. The catalyst also exists after the curable film is cured. In other words, when the curable film obtained by the method for producing a curable film of the present invention contains a catalyst, the cured product obtained by curing the curable film also contains the catalyst.
[0018] The content of the catalyst is not particularly limited, but is preferably 0.01 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the silsesquioxane. By setting the content of the catalyst within the above range, curing can be further promoted and decomposition of the cured product due to high-temperature treatment can be further suppressed. The content of the catalyst is more preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, more preferably 7 parts by weight or less, and even more preferably 5 parts by weight or less relative to 100 parts by weight of the silsesquioxane.
[0019] The curable resin composition may contain a crosslinking agent. When the curable resin composition contains a crosslinking agent, the crosslinking agent crosslinks between the curable resins, increasing the crosslink density of the cured product, and further suppressing decomposition at high temperatures. As a result, the substrate can be prevented from warping or cracking, and the connection reliability can be further improved. Examples of the crosslinking agent include alkoxysilane compounds such as dimethoxysilane compounds, trimethoxysilane compounds, diethoxysilane compounds, and triethoxysilane compounds, or silicate oligomers obtained by condensation of tetramethoxysilane compounds and tetraethoxysilane compounds. Among them, polyalkoxysilane is preferred from the viewpoint of improving crosslink density and heat resistance.
[0020] The content of the crosslinking agent is not particularly limited, but is preferably 1 part by weight or more and 50 parts by weight or less relative to 100 parts by weight of the silsesquioxane. By setting the content of the crosslinking agent within the above range, the crosslinking density of the cured product can be set within a suitable range. The content of the crosslinking agent is more preferably 3 parts by weight or more, more preferably 3.2 parts by weight or more, more preferably 30 parts by weight or less, and even more preferably 20 parts by weight or less relative to 100 parts by weight of the silsesquioxane.
[0021] The curable resin composition preferably contains a heat-resistant resin. By using a heat-resistant resin in the curable resin composition, it is possible to obtain a cured product that is less likely to crack when subjected to high-temperature treatment, even when the curable film is made into a thick curable film.
[0022] Examples of the heat-resistant resin include polyimide, epoxy resin, silicone resin, benzoxazine resin, cyanate resin, and phenolic resin, and polyimide is particularly preferred from the viewpoint of heat resistance.
[0023] The molecular weight of the heat-resistant resin is not particularly limited, but is preferably 5000 or more and 150000 or less. By having the weight-average molecular weight of the heat-resistant resin in the above range, even if it is made into a thick curable film, it is possible to obtain a cured product that is less likely to crack during high-temperature treatment. The molecular weight of the heat-resistant resin is more preferably 10000 or more, more preferably 30000 or more, more preferably 100000 or less, and even more preferably 70000 or less.
[0024] The content of the heat-resistant resin is preferably 0.5 parts by weight or more and 50 parts by weight or less based on 100 parts by weight of the silsesquioxane. By setting the content of the heat-resistant resin within the above range, even if it is made into a thick curable film, it is possible to obtain a cured product that is less likely to crack when treated at high temperatures.The content of the heat-resistant resin is more preferably 0.7 parts by weight or more, more preferably 0.75 parts by weight or more, particularly preferably 1 part by weight or more, more preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and particularly preferably 5 parts by weight or less, relative to 100 parts by weight of the silsesquioxane.
[0025] When the heat-resistant resin is a polyimide, the polyimide preferably has a siloxane bond. When the polyimide has a siloxane bond, the compatibility with the silsesquioxane is increased, so that unevenness (surface roughness) caused by precipitation of the polyimide during application can be further suppressed.
[0026] When the polyimide has a siloxane bond, the polyimide preferably has a ratio of carbon atoms to silicon atoms in the main chain structure, C / Si, of 17 or less. When the ratio of carbon atoms to silicon atoms in the main chain structure of the polyimide falls within the above range, compatibility with the silsesquioxane is further improved, and surface roughness can be further suppressed during application. The C / Si is more preferably 16.5 or less, and even more preferably 16 or less. There is no particular lower limit for the C / Si, but from the viewpoint of practical use and of further improving heat resistance at 400°C, it is preferably 4 or more. The ratio C / Si of carbon atoms to silicon atoms in the main chain structure of the polyimide is the ratio of C and Si in the repeating unit, and does not include C and Si at both ends. The C / Si is also 1 H-NMR, 13 C-NMR and 29 The structure of the polyimide is obtained by Si-NMR, and the number of C atoms and Si atoms in the repeating unit of the main chain is measured to determine the amount of C atoms.
[0027] The polyimide preferably has an oxazine ring or imide ring structure at least at one of its terminals, and more preferably has an oxazine ring or imide ring structure at both terminals. By having an oxazine ring or imide ring structure at the terminal of the polyimide, surface roughness can be further suppressed when the polyimide is made into a thick film. The oxazine ring and imide ring structures may have a substituent. Among them, it is more preferable that the polyimide has any one of the structures shown in the following structural formulae (2) to (7) at at least one terminal, and it is particularly preferable that both terminals have any one of the structures shown in the following structural formulae (2) to (7). Note that "*" in the following structural formulae represents a bonding site with a portion other than the terminal of the polyimide.
[0028] [ka]
[0029] The polyimide preferably has a weight average molecular weight of 1,000 or more and 50,000 or less. When the weight average molecular weight of the polyimide is within the above range, the compatibility with the silsesquioxane is improved, and the handleability can be further improved. The weight average molecular weight is more preferably 2000 or more, even more preferably 3000 or more, more preferably 35000 or less, and even more preferably 30000 or less. The weight-average molecular weight of the polyimide is measured as a polystyrene-equivalent molecular weight by gel permeation chromatography (GPC) using THF as an elution solvent and a Time-MB-M6.0×150 mm (manufactured by Waters Corporation) or an equivalent column, and can be calculated with a polystyrene standard.
[0030] The content of the polyimide is preferably 0.5 parts by weight or more and 50 parts by weight or less with respect to 100 parts by weight of the silsesquioxane. By setting the polyimide content within the above range, even if it is made into a thick curable film, it is possible to obtain a cured product that is less likely to crack during high-temperature treatment.The content of the polyimide is preferably 0.7 parts by weight or more, more preferably 0.75 parts by weight or more, and even more preferably 1 part by weight or more, and is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and even more preferably 5 parts by weight or less, relative to 100 parts by weight of the silsesquioxane.
[0031] The curable resin composition preferably contains a filler. The mechanical properties of the cured product can be suitably controlled by using a filler in the curable resin composition. The filler is not particularly limited as long as it has no electrical conductivity, and examples of the filler include silica filler and glass fiber.
[0032] The content of the filler is more preferably 15 parts by weight or more, even more preferably 20 parts by weight or more, more preferably 40 parts by weight or less, and even more preferably 35 parts by weight or less, based on 100 parts by weight of the silsesquioxane. The content of the silica filler is preferably 15 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the silsesquioxane. By setting the content of the filler within the above range, warping and cracking of the substrate can be further suppressed. Furthermore, when the filler is a silica filler, the content of the silica filler is more preferably 20 parts by weight or more, and even more preferably 25 parts by weight or more, more preferably 35 parts by weight or less, and even more preferably 30 parts by weight or less, per 100 parts by weight of the silsesquioxane.
[0033] The curable resin composition may contain other additives such as a viscosity modifier and an adhesion promoter, if necessary, within the range that does not impair the effects of the present invention.
[0034] The solvent is not particularly limited as long as it can dissolve the silsesquioxane and the components of the curable resin composition, and specific examples include ethyl acetate, methyl ethyl ketone, hexane, heptane, etc. Among them, the solvent is preferably one having a low boiling point, since it can easily satisfy the temperature of the drying step described below and makes it difficult for unintended curing of the curable resin composition to occur during the drying step.
[0035] The solvent preferably has a boiling point of less than 100°C. By using a solvent with a boiling point of less than 100°C, the temperature required for the drying process described below can be more easily met, and polyethylene terephthalate, which has an excellent balance of availability, cost, and heat resistance, can be used for the support film. The boiling point of the solvent is more preferably 90° C. or lower. The lower limit of the boiling point of the solvent is not particularly limited, but from the viewpoint of the handleability of the resulting solution, it is preferably 70° C. or higher. Examples of the solvent having a boiling point of less than 100° C. include ethyl acetate, methyl ethyl ketone, hexane, and heptane.
[0036] The viscosity of the solution is preferably 1000 mPa s or more and 1500 mPa s or less from the viewpoint of improving the wettability to the release-treated surface of the support film while ensuring the coatability to the support film. The viscosity of the solution can be measured by measuring the kinetic viscosity at 25°C and 10.0 rpm shear using an E-type viscometer (TVE25H, manufactured by Toki Sangyo Co., Ltd., or an equivalent product).
[0037] The solution preferably has a solids concentration of 50% by weight or more. By setting the solid content concentration of the solution to 50% by weight or more, the wettability to the release-treated surface of the support film can be improved, and the curable resin composition can be more easily formed into a film. The solid content concentration of the solution is more preferably 55% by weight or more, and even more preferably 60% by weight or more. The upper limit of the solid content concentration of the solution is not particularly limited, but is preferably 80% by weight or less from the viewpoint of application to the support film.
[0038] The method for producing a curable film of the present invention then includes a step of applying the solution onto the release-treated surface of a support film that has been subjected to a release treatment so that the solution has a dry thickness of 50 μm or more. By applying the solution obtained in the above-mentioned solution preparation step onto a support film so that the thickness after drying is 50 μm or more, the resulting curable film can sufficiently fill in the step even when used on a substrate having a large step. In addition, by making the curable film thick, a uniform film can be obtained. The method of application is not particularly limited, and any conventionally known method such as blade coating or spin coating can be used. In this specification, the support film refers to a film that has been subjected to a release treatment on the surface on which the above-mentioned solution or a resin layer described below is laminated.
[0039] The support film is appropriately selected according to the boiling point of the solvent and can withstand the temperature in the drying step described below. Examples of the support film include polyethylene terephthalate, polyethylene naphthalate, etc. Among them, the support film preferably contains polyethylene terephthalate, and more preferably consists of polyethylene terephthalate, because it has an excellent balance of availability, cost, and heat resistance.
[0040] The thickness of the solution after drying is preferably 75 μm or more, more preferably 100 μm or more, because the solution can sufficiently fill the step even when used on a substrate having a larger step. The upper limit of the thickness of the solution after drying is not particularly limited, but is preferably 300 μm or less from the viewpoint of thickness uniformity and retention of the roll shape.
[0041] The method for producing a curable film of the present invention then includes a step of drying the applied solution at a temperature of T+50° C. or higher for 10 minutes or longer. By drying the solution under the above conditions, a curable film from which the solvent has been sufficiently removed can be obtained even in the case of a thick curable film. From the viewpoint of sufficiently drying the solution even in the case of a thicker curable film, the drying temperature is preferably T+60°C or higher, more preferably T+70°C or higher. The upper limit of the drying temperature is not particularly limited as long as it is equal to or lower than the temperature at which the curable resin composition is cured, but is preferably T+100°C or lower from the viewpoints of the dryness of the solution, the range of materials for the support film, and costs. From the same viewpoint, the drying time is preferably 15 minutes or more, and preferably 30 minutes or less. The heating furnace (oven) used for the drying and the heating and heating described later is not particularly limited as long as it can maintain each temperature for each time.
[0042] The present invention also includes a curable film obtained by the curable film manufacturing method of the present invention, i.e., a curable film having a support film that has been subjected to a release treatment and a resin layer laminated on the release-treated surface of the support film, wherein the resin layer contains a silsesquioxane represented by structural formula (1) and the thickness of the resin layer is 50 μm or more. By using the cured resin layer as an insulating layer in a semiconductor device in which a plurality of semiconductor chips or substrates are stacked, it is possible to exhibit excellent heat resistance and excellent step filling performance even when used on a substrate having large irregularities. The silsesquioxane is the same as the silsesquioxane in the method for producing the curable film of the present invention. In addition, the components of the resin layer other than the silsesquioxane may be the same as those in the curable resin composition.
[0043] The thickness of the resin layer is preferably 70 μm or more, more preferably 100 μm or more, because the resin layer can sufficiently fill the step even when used on a substrate having a larger step. The upper limit of the thickness of the resin layer is not particularly limited, but is preferably 300 μm or less from the viewpoints of thickness uniformity and retention of the roll shape.
[0044] Examples of the support film include polyethylene terephthalate, polyethylene naphthalate, etc. Among them, the support film preferably contains polyethylene terephthalate, and more preferably consists of polyethylene terephthalate, because it has an excellent balance of availability, cost, and heat resistance.
[0045] The thickness of the support film is not particularly limited, but from the viewpoint of handleability, it is preferably 25 μm or more, more preferably 50 μm or more, and is preferably 200 μm or less, more preferably 100 μm or less.
[0046] In the curable film of the present invention, it is preferable that the relationship tr>tf is satisfied, where tr is the thickness of the resin layer and tf is the thickness of the support film. The curable film of the present invention is preferably used in a manner in which the resin layer is laminated on a substrate in a state in which the support film is present, and then the support film is peeled off, from the viewpoint of ease of handling and production efficiency. In this case, if the resin layer is thicker than the support film, the resin layer is more likely to extend over the entire substrate, and the unevenness embedding performance can be further improved. The ratio of the thickness of the resin layer to the thickness of the support film, that is, tr / tf, is preferably 1.5 or more, more preferably 2.5 or more, since the resin layer is more likely to extend over the entire substrate. In addition, in order to improve the ease of handling and to laminate by applying an even force to the entire substrate, it is preferably 4 or less, more preferably 3.5 or less.
[0047] In the curable film of the present invention, the resin layer is preferably heated at 300° C. for 1 hour in the atmosphere to heat-set the cured product, which has a glass transition temperature of 25° C. or higher and 100° C. or lower. Since the cured product of the curable film of the present invention has a glass transition temperature in the above range, the resin layer can be laminated at a temperature higher than the glass transition temperature, so that the resin can easily reach the stepped portion and fill the stepped portion without voids. The glass transition temperature of the cured product is more preferably 40°C or higher, even more preferably 50°C or higher, more preferably 80°C or lower, and even more preferably 70°C or lower.
[0048] By using the curable film of the present invention in a laminate for a substrate, it is possible to obtain an insulating layer that has excellent heat resistance and excellent step filling performance even when used on a substrate having large irregularities. The present invention also includes a laminate having an organic layer made of a cured product of the resin layer of the curable film of the present invention on the first surface of a substrate having a first surface with projections and recesses and a second surface that is the opposite surface of the substrate.
[0049] The laminate of the present invention is a laminate having a substrate having a first surface having projections and recesses and a second surface which is the opposite surface of the substrate, the laminate having an organic layer formed of a cured product of the resin layer of the curable film of the present invention on the first surface. The organic layer serves as an insulating layer between each element or substrate in a semiconductor device in which a plurality of elements or substrates are stacked. Conventional insulating layers use hard inorganic materials to withstand high-temperature treatment during manufacturing, so that when the substrate is deformed, the stress cannot be relieved and the substrate is prone to warping or cracking. In the laminate of the present invention, by using a silsesquioxane having a specific structure having flexibility capable of relieving stress as an insulating layer, the substrate is less likely to warp or crack, and the connection reliability between the substrates can be improved. In addition, since the organic layer of the laminate of the present invention is made of the cured product of the curable film of the present invention, there is no process of drying the solvent in the production of the laminate. Therefore, compared with the case of forming an organic layer by applying a curable resin composition, voids due to shrinkage of the organic layer due to volatilization of the solvent are less likely to occur, so that even a substrate having large irregularities can exhibit high connection reliability.
[0050] The substrate is not particularly limited, and may be a circuit substrate on which elements and wiring are formed, such as a sensor circuit substrate on which a pixel portion (pixel region) is provided, a circuit substrate on which a peripheral circuit portion such as a logic circuit that executes various signal processes related to the operation of the solid-state imaging device is mounted, or a circuit substrate on which a peripheral circuit such as a memory circuit is mounted.
[0051] Examples of the unevenness include unevenness caused by a substrate or chip, unevenness caused by electrodes, and the like.
[0052] The height of the unevenness is not particularly limited, but since the laminate of the present invention has high connection reliability of the organic layer even on a substrate having large unevenness, the height of the unevenness of the substrate is preferably 30 μm or more, more preferably 50 μm or more, and even more preferably 70 μm or more. The upper limit of the height of the unevenness of the substrate is not particularly limited, but from the viewpoint of filling the step, it is preferably 100 μm or less.
[0053] The use of the laminate of the present invention is not particularly limited, but it is suitable for an imaging device or a semiconductor device. Such an imaging device having the laminate of the present invention and a semiconductor device having the laminate of the present invention are also part of the present invention.
[0054] The method for producing the laminate of the present invention is not particularly limited, and it can be produced, for example, by a method in which a cured product of the curable film of the present invention is laminated onto the first surface of the substrate. The present invention also provides a method for producing a laminate, which includes the steps of heating the curable film of the present invention to a temperature equal to or higher than the glass transition temperature of the resin layer, and laminating the resin layer onto a first surface of a substrate having a first surface having irregularities and a second surface opposite the first surface, peeling a support film from the curable film after lamination, and heating the substrate with the resin layer laminated thereon to form an organic layer made of a cured product of the resin layer on the substrate.
[0055] The method for producing the laminate of the present invention first involves heating the curable film of the present invention to a temperature equal to or higher than the glass transition temperature of the resin layer, and laminating the resin layer onto a first surface of a substrate having an uneven first surface and an opposite second surface. By heating the resin layer to a temperature equal to or higher than the glass transition temperature when laminating the resin layer onto the first surface of the substrate, the cured product can be easily spread over the entire substrate, thereby improving the ability to fill irregularities.
[0056] From the viewpoint of a balance between the effect of improving the performance of embedding irregularities and the ease of lamination, the heating temperature is preferably at least +10°C above the glass transition temperature, more preferably at least +20°C above the glass transition temperature, and is preferably at most +50°C above the glass transition temperature.
[0057] The step of laminating the resin layer of the curable film is carried out in a state in which a support film is provided. The resin layer is heated without peeling off the support film, and laminated onto the substrate, thereby improving production efficiency. In this case, by setting the ratio of the thickness of the resin layer to the thickness of the support film within the above range, the resin layer is easily spread over the entire substrate, and the unevenness filling performance can be further improved.
[0058] The lamination method may be, for example, vacuum lamination.
[0059] The method for producing a laminate of the present invention then includes a step of peeling the support film from the curable film after lamination. As described above, after the step of laminating the resin layer of the curable film with the support film in place is performed, the support film is peeled off.
[0060] The method for producing a laminate of the present invention then carries out a step of heating the substrate on which the resin layer has been laminated to form an organic layer made of a cured product of the resin layer on the substrate. The organic layer is formed by curing the resin layer. The heating temperature in the step of forming the organic layer is preferably 200° C. or higher, more preferably 250° C. or higher, and more preferably 350° C. or lower, and more preferably 300° C. or lower. The heating time in the step of forming the organic layer is preferably 30 minutes or longer, more preferably 60 minutes or longer, and preferably 120 minutes or shorter.
[0061] A more specific embodiment of the laminate of the present invention is a laminate in which the substrate is a first substrate having a plurality of chips on a first surface (hereinafter, also referred to as laminate A). In the laminate A, the unevenness of the substrate is formed by the plurality of chips.
[0062] The laminate A preferably has an inorganic layer on the surface of the organic layer on the side where the first substrate is not laminated. By providing an inorganic layer on the organic layer as an auxiliary insulating layer, moisture in the atmosphere is less likely to permeate than an organic layer alone, so that high connection reliability can be achieved even under high temperature and high humidity. In addition, since the connection reliability is improved under high temperature and high humidity, it is preferable that the inorganic layer covers the entire exposed surface of the organic layer. In addition, since the inorganic layer of the laminate of the present invention is thin, the organic layer does not hinder the elimination of warpage of the substrate.
[0063] The material for the inorganic layer is not particularly limited, and examples thereof include SiN, SiO2, Al2O3, etc. Among these, SiN and SiO2 are preferred because of their excellent insulating properties and heat resistance.
[0064] From the viewpoint of further enhancing connection reliability, the thickness of the inorganic layer is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more, and is preferably 1 μm or less, more preferably 500 nm or less, and even more preferably 100 nm or less.
[0065] The laminate A may have a support substrate on the surface of the inorganic layer on which the organic layer is not laminated. By laminating a support substrate on the inorganic layer, it becomes easy to fix an electronic component including the laminate of the present invention, such as an imaging device or semiconductor device, to a housing. The supporting substrate may be made of glass, single crystal silicon, or the like.
[0066] The laminate A may further include a second substrate on the second surface side of the first substrate, and the first substrate and the second substrate may be electrically connected to each other. In the laminate A, the organic layer prevents the first substrate from warping or cracking, and therefore the second substrate further laminated on the first substrate is also prevented from warping or cracking, thereby improving connection reliability. The second substrate may be the same as the first substrate.
[0067] Here, a schematic diagram showing an example of the laminate A is shown in FIG. 1. As shown in FIG. 1, the laminate A has a structure in which an organic layer 3 is laminated on the surface (first surface) of a first substrate 1 having a plurality of chips 2 on which chips are laminated, and the organic layer 3 acts as an insulating layer. Since the organic layer 3 of the laminate A is made of a cured product of a curable film, voids caused by shrinkage of the organic layer due to volatilization of the solvent are unlikely to occur, and therefore high connection reliability can be achieved even with a substrate having large irregularities. In addition, the laminate A may have an inorganic layer 4 on the surface of the organic layer 3 on which the first substrate is not laminated. By providing the inorganic layer 4 on the organic layer 3, high connection reliability can be achieved even under high temperature and high humidity. Furthermore, the laminate A of the present invention may have a support substrate 5 laminated on the surface of the inorganic layer 4 on which the organic layer is not laminated, and a second substrate 6 may be laminated on the second surface of the first substrate 1, and the first substrate 1 and the second substrate 6 may be electrically connected. In addition, although the organic layer 3 and the inorganic layer 4 are each a single layer in FIG. 1, they may each be made up of multiple layers.
[0068] The laminate A can be produced by, in addition to the method for producing the laminate, optionally performing a step of forming an inorganic layer on the organic layer, a step of further bonding a support substrate onto the inorganic layer, a step of laminating a second substrate on the second surface of the first substrate, and a step of electrically connecting the first substrate and the second substrate.
[0069] Methods for forming the inorganic layer include chemical vapor deposition (CVD), sputtering, deposition, and the like.
[0070] The first and second substrates may be electrically connected by a method of melting and connecting the electrodes of the first and second substrates by heat treatment, etc. The heat treatment is usually performed at 400° C. for about 4 hours.
[0071] A more specific embodiment of the laminate is a laminate in which the substrate has an electrode, and the organic layer is disposed between two substrates having electrodes. The present invention also includes such a laminate (hereinafter also referred to as laminate B) having an organic layer made of a cured product of the resin layer of the curable film of the present invention between a third substrate having an electrode and a fourth substrate having an electrode, wherein the electrode of the third substrate and the electrode of the fourth substrate are electrically connected via a through hole penetrating the organic layer.
[0072] The laminate B of the present invention is a laminate having an organic layer composed of a cured product of the resin layer of the curable film of the present invention between a third substrate having an electrode and a fourth substrate having an electrode, and the electrode of the third substrate and the electrode of the fourth substrate are electrically connected via a through hole penetrating the organic layer. The organic layer provided between the electrode of the third substrate (hereinafter also referred to as the first electrode) and the electrode of the fourth substrate (hereinafter also referred to as the second electrode) acts as an insulating layer, thereby suppressing short circuit of current. In addition, since the organic layer of the laminate B of the present invention is made of a cured product of a curable film, voids caused by shrinkage of the organic layer due to volatilization of the solvent are unlikely to occur, and therefore high connection reliability can be achieved even with substrates having large irregularities. Here, being electrically connected refers to a state in which the first electrode and the second electrode are connected by a conductive material or the like filled in the through hole.
[0073] The third and fourth substrates may be the same as the above substrate.
[0074] The materials of the electrodes of the third substrate and the fourth substrate and the conductive material are not particularly limited, and conventionally known electrode materials such as gold, copper, and aluminum can be used.
[0075] The laminate B of the present invention preferably has an inorganic layer between the third substrate and the fourth substrate. By providing an inorganic layer as an auxiliary insulating layer on the organic layer, moisture in the air is less likely to permeate than an organic layer alone, so that high connection reliability can be achieved even under high temperature and high humidity. The inorganic layer can be the same as the inorganic layer of the laminate A. In addition, since the connection reliability is improved under high temperature and high humidity, it is preferable that the inorganic layer covers the exposed surface of the organic layer, that is, the entire side surface. In addition, since the inorganic layer of the laminate of the present invention is thin, the organic layer does not hinder the elimination of warpage of the substrate.
[0076] The laminate B of the present invention preferably has a barrier metal layer on the surface of the through hole. The barrier metal layer serves to prevent the conductive material (e.g., Cu atoms in the case of a Cu electrode) filled in the through-hole from diffusing into the organic layer. By providing a barrier metal layer on the surface of the through-hole, the conductive material filling the through-hole is covered with the barrier metal layer except for the surface in contact with the electrode, so that short circuits and poor conduction caused by the diffusion of the conductive material into the organic layer can be further suppressed. The material of the barrier metal layer can be a known material such as tantalum, tantalum nitride, titanium nitride, silicon oxide, silicon nitride, etc.
[0077] The thickness of the barrier metal layer is not particularly limited, but from the viewpoint of further improving the connection reliability of the laminate, it is preferably 1 nm or more, more preferably 10 nm or more, more preferably 100 nm or less, and even more preferably 50 nm or less.
[0078] Here, a schematic diagram showing an example of the laminate B of the present invention is shown in FIG. 2. As shown in FIG. 2, the laminate B of the present invention has a structure in which a third substrate 7 having an electrode 8 and a fourth substrate 9 are bonded via an organic layer 3, and the electrodes 8 on the third substrate 7 and the fourth substrate 9 are electrically connected through a conductive material filled in a through hole 10 provided in the organic layer 3. The laminate B of the present invention may also have an inorganic layer 4 as an auxiliary insulating layer between the third substrate and the fourth substrate, and the moisture resistance can be improved by providing the inorganic layer 4. If the inorganic layer 4 covers the entire side surface of the organic layer 3, the moisture resistance can be further improved. Furthermore, the laminate B of the present invention may have a barrier metal layer 11 provided on the surface of the through hole 10. If the barrier metal layer 11 is provided, the conductive material filled in the through hole 10 is less likely to diffuse into the organic layer 3, so that short circuits and poor conduction can be further suppressed. In FIG. 2, the inorganic layer 4 is provided on each of the organic layers 3 on the third substrate 7 side and the fourth substrate 9 side, but it may be provided on only one of them.
[0079] The present invention also provides a method for producing a laminate B, the method comprising the steps of heating the curable film of the present invention to a temperature equal to or higher than the glass transition temperature of a resin layer, and laminating the resin layer on the electrode-bearing surfaces of a third substrate having an electrode and a fourth substrate having an electrode, peeling a support film from the curable film after lamination, heating the third substrate and the fourth substrate on which the resin layer has been laminated to form organic layers composed of a cured product of the resin layer on the third substrate and the fourth substrate, forming through holes in each of the organic layers, filling each of the through holes with a conductive material, polishing the surfaces of the third substrate and the fourth substrate on which the conductive material has been filled to form bonding electrodes, and bonding the third substrate and the fourth substrate together so that the bonding electrodes are bonded to each other.
[0080] The method for producing laminate B of the present invention first includes the steps of heating a curable film to a temperature equal to or higher than the glass transition temperature of a resin layer, and laminating the resin layer onto the electrode-bearing surfaces of a third substrate having an electrode and a fourth substrate having an electrode, peeling a support film from the curable film after lamination, and heating the third substrate and the fourth substrate on which the resin layer is laminated to form organic layers composed of a cured product of the resin layer on the third substrate and the fourth substrate. These steps are the same as those of the manufacturing method of the laminate A described above, except that a third substrate having an electrode and a fourth substrate having an electrode are used as substrates.
[0081] The method for producing the laminate B of the present invention then carries out a step of forming through holes in each of the organic layers and the inorganic layers. The through-hole may be patterned. The method for forming the through-hole is not particularly limited, and the through-hole may be formed by laser irradiation such as CO2 laser or etching. When other layers are formed on the electrode surface of the substrate, the through-hole is formed so as to penetrate the other layers and expose the electrode surface of the substrate.
[0082] The method for producing the laminate B of the present invention then includes a step of forming an inorganic layer and / or a barrier metal layer, if necessary. The inorganic layer and the barrier metal layer can be formed by chemical vapor deposition (CVD), sputtering, deposition, or the like. The step of forming the inorganic layer is preferably carried out before and / or after the step of laminating the cured product, and the step of forming the barrier metal layer is preferably carried out after the step of forming the through holes.
[0083] The method for producing the laminate B of the present invention then includes a step of filling each of the through holes with a conductive material. The method for filling the through holes with the conductive material may be plating or the like. The conductive material may be the same as the conductive material of the laminate B of the present invention.
[0084] The method for producing the laminate B of the present invention then includes a step of polishing the surfaces of the third substrate having the electrode and the fourth substrate having the electrode, the surfaces being filled with the conductive material, to form bonding electrodes. The conductive material formed in the unnecessary portion is removed by grinding to form a bonding electrode connecting the electrodes formed on the two elements. The polishing is preferably performed by planarizing and removing the layer formed of the conductive material until the organic layer is exposed, or until the inorganic layer, if any, is exposed. The polishing method is not particularly limited, and for example, a chemical mechanical polishing method can be used.
[0085] The method for producing laminate B of the present invention then carries out a step of bonding the third substrate having the electrode and the fourth substrate having the electrode together so that the bonding electrodes of the third substrate having the electrode are bonded to each other. The third substrate and the fourth substrate may be bonded to each other by a method of melting and connecting the electrodes and the connection electrodes by heat treatment, etc. The heat treatment is usually performed at 400° C. for about 4 hours. Effect of the Invention
[0086] According to the present invention, it is possible to provide a method for producing a curable film that can form a uniform film on a support film, and the cured film has excellent heat resistance and can exhibit excellent step-filling performance even when used on a substrate having large irregularities, a curable film obtained by the method for producing a curable film, a laminate using the curable film, an imaging device and a semiconductor device having the laminate, and a method for producing the laminate. [Brief description of the drawings]
[0087] [Figure 1] FIG. 1 is a schematic diagram showing an example of a laminate A of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a laminate B of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0088] The following examples further illustrate the present invention, but are not intended to limit the scope of the present invention.
[0089] (Production of Silsesquioxane (Resin A)) In a reaction vessel equipped with a reflux condenser, a thermometer, and a dropping funnel, 65.4 g of phenyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd., molecular weight 198.29), 8.8 g of sodium hydroxide, 6.6 g of water, and 263 mL of 2-propanol were added. Heating was started with stirring under a nitrogen stream. Stirring was continued for 6 hours from the start of reflux, and then the mixture was left to stand overnight at room temperature. The reaction mixture was then transferred to a filter, pressurized with nitrogen gas, and filtered. The obtained solid was washed once with 2-propyl alcohol, filtered, and dried under reduced pressure at 80°C to obtain 33.0 g of a colorless solid (DD-ONa).
[0090] In a 300 ml three-neck flask equipped with a dropping funnel, reflux condenser, and thermometer, 11.6 g of the compound (DD-ONs), 100 g of tetrahydrofuran, and 3.0 g of triethylamine were charged and sealed with dry nitrogen. While stirring with a magnetic stirrer, 4.5 g:30 mmol of methyltrichlorosilane was dropped at room temperature. Then, the mixture was stirred at room temperature for 3 hours. 50 g of water was added to the reaction solution to dissolve the generated sodium chloride and hydrolyze the unreacted methyltrichlorosilane. The reaction mixture thus obtained was separated, and the organic layer was washed once with 1N hydrochloric acid, once with a saturated aqueous solution of sodium bicarbonate, and then washed three times with ion-exchanged water. The organic layer after washing was dried over anhydrous magnesium sulfate and concentrated under reduced pressure with a rotary evaporator to obtain 7.1 g of a white powdery solid (DD(Me)-OH).
[0091] A 100 mL flask was equipped with a cooling tube, a mechanical stirrer, a Dean-Stark tube, an oil bath, and a thermometer protection tube, and the inside of the flask was replaced with nitrogen. 5.0 g of DD(Me)-OH, 11.6 g of octamethylcyclotetrasiloxane (D4), 3.9 g of sulfuric acid, 52 g of toluene, and 13 g of 4-methyltetrahydropyran were placed in the flask. After stirring at 100°C for 5 hours, water was poured into the reaction mixture, and the aqueous layer was extracted with toluene. The combined organic layer was washed with water, an aqueous sodium bicarbonate solution, and saturated saline, and then dried with anhydrous sodium sulfate. This solution was concentrated under reduced pressure, and the residue was reprecipitated in a solution mixed with 2-propanol:ethyl acetate = 50:7 (weight ratio), purified, and dried to obtain a silsesquioxane (resin A, weight average molecular weight: 36000) having the structure of the following structural formula (8), m is 27, and n is 4 on average.
[0092] [ka]
[0093] (Production of Resin B) A 100 mL flask was equipped with a cooling tube, a mechanical stirrer, a Dean-Stark tube, an oil bath, and a thermometer protection tube, and the inside of the flask was replaced with nitrogen. 5.0 g of DD(Me)-OH, 11.2 g of octamethylcyclotetrasiloxane (D4), 3.9 g of sulfuric acid, 52.0 g of toluene, and 13.0 g of 4-methyltetrahydropyran were placed in the flask. After stirring at 100°C for 5 hours, water was poured into the reaction mixture, and the aqueous layer was extracted with toluene. The combined organic layer was washed with water, an aqueous sodium bicarbonate solution, and saturated saline, and then dried with anhydrous sodium sulfate. This solution was concentrated under reduced pressure, and the residue was reprecipitated in a solution mixed with 2-propanol:ethyl acetate = 50:7 (weight ratio), purified, and dried to obtain an organosilicon compound (resin B, weight average molecular weight 46000) having the structure of the above formula (8), m is 36, and n is 3 on average.
[0094] (Manufacture of Resin C) 250 mL of toluene was added to a 500 mL round-bottom flask equipped with a Teflon stirrer. Then, 35 g (0.35 mol) of triethylamine and 35 g (0.36 mol) of methanesulfonic anhydride were added and stirred to form a salt. After stirring for 10 minutes, 56 g (0.1 mol) of dimer diamine (Croda, Priamine 1075) and 19.1 g (0.09 mol) of pyromellitic anhydride were added in that order. A Dean-Stark trap and condenser were attached to the flask, and the mixture was refluxed for 2 hours to form an amine-terminated diimide. After cooling the reactants below room temperature, 12.8 g (0.13 mol) of maleic anhydride was added, followed by 5 g (0.05 mol) of methanesulfonic anhydride. The mixture was refluxed for an additional 12 hours, cooled to room temperature, and 300 mL of toluene was added to the flask, which was then left to settle and remove impurities. The resulting solution was filtered through a glass frit funnel filled with silica gel, and the solvent was then removed in vacuum to obtain an amber wax-like resin C represented by the following formula (9). The weight average molecular weight of the obtained compound was measured by gel permeation chromatography (GPC) using THF as an eluent and HR-MB-M (product name, manufactured by Waters Corporation) as a column, and was found to be 5000. In addition, h in the following formula (9) represents the number of repeating units.
[0095] [ka]
[0096] (Manufacture of Resin D) 120.0 g of tetracarboxylic dianhydride 4,4'-(Hexafluoroisopropylidene)diphthalic anhydride (Tokyo Chemical Industry Co., Ltd., molecular weight 444.24) and 400 g of toluene were placed in a reaction vessel equipped with a stirrer, a water divider, a thermometer, and a nitrogen gas inlet, and the solution in the reaction vessel was heated to 60°C. Next, 207.3 g of aromatic diamine 2,2-Bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (Tokyo Chemical Industry Co., Ltd., molecular weight 518.46) was added to the reaction vessel. A Dean-Stark trap and a condenser were attached to the flask, and the mixture was heated under reflux for two hours to obtain an imide compound with amines at both ends. Next, an excess amount of phenol and paraformaldehyde were added to the reaction solution, and the resulting mixture was refluxed for another 12 hours to convert the ends to benzoxazine. After the reaction was completed, isopropanol was added to cause reprecipitation, and the precipitate was collected and dried. In this way, a compound having a benzoxazine structure (resin D, weight average molecular weight 50,000) was obtained, which has an imide skeleton and a benzoxazine structure at the end, and has the structure of the following formula (10). Note that i in the following formula (10) represents the number of repeating units.
[0097] [ka]
[0098] (Manufacture of Resin E (heat-resistant resin)) A 100 mL flask was equipped with a cooling tube, a mechanical stirrer, a Dean-Stark tube, an oil bath, and a thermometer protection tube. 11.1 g of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) (manufactured by Daikin Corporation), 7.8 g of bisaminopropyltetramethyldisiloxane (PAM-E, manufactured by Shin-Etsu Silicone Co., Ltd.), and 92.1 g of anisole were added to the flask and stirred. The flask was heated at 100°C for 1 hour, and then refluxed in an oil bath at 170°C for 1 hour. The solution was cooled to room temperature, 1.3 g of citraconic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred at 120°C for 10 minutes, and then refluxed in an oil bath at 170°C for 1 hour to obtain a heat-resistant resin (resin E, weight average molecular weight: 9900) having the structure of the following structural formula (11). In addition, j in the following structural formula (11) represents the number of repeating units.
[0099] [ka]
[0100] (Manufacture of Resin F (heat-resistant resin)) 250 mL of toluene was added to a 500 mL round bottom flask equipped with a Teflon stirrer. Then, 35 g (0.35 mol) of triethylamine and 35 g (0.36 mol) of methanesulfonic anhydride were added and stirred to form a salt. After stirring for 10 minutes, 31.9 g (0.06 mol) of dimer diamine (Croda, Priamine 1075), 5.5 g (0.015 mol) of Bis-AP-AF, and 39 g (0.075 mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added in this order. A Dean-Stark trap and condenser were attached to the flask, the mixture was refluxed for 2 hours, cooled to room temperature, and 300 mL of toluene was added to the flask, and impurities were precipitated and removed by standing. The resulting solution was filtered through a glass frit funnel filled with silica gel, and the solvent was then removed in vacuum to obtain a brown solid resin F having two partial structures represented by the following formula (12). The weight average molecular weight of the obtained resin was measured by gel permeation chromatography (GPC) using THF as an eluent and an HR-MB-M (Waters Corporation) column, and was found to be 72000. In addition, s and t in the following formula (12) represent the number of repeating units.
[0101] [ka]
[0102] Example 1 (1) Preparation of solutions A solution was obtained by adding and mixing 100 parts by weight of the resin A obtained as the base resin, 1 part by weight of the heat-resistant resin (resin E) obtained, 0.1 parts by weight of the catalyst, and 15 parts by weight of the filler with a solvent so that the solid content concentration was 65% by weight. The details of each raw material used are as follows. Catalyst: ZC-162, an acetylacetonate complex with zirconium as the central metal, manufactured by Matsumoto Fine Chemical Co., Ltd. Filler: Silica filler, MT-10, manufactured by Tokuyama Corporation, Solvent: Ethyl acetate (boiling point 77°C)
[0103] (2) Viscosity measurement The kinetic viscosity of the solution was measured at 25° C. and 10.0 rpm shear using an E-type viscometer (TVE25H, manufactured by Toki Sangyo Co., Ltd.).
[0104] (3) Manufacturing of curable films A 50 μm-thick PET film that had been subjected to a release treatment was prepared as a support film. The obtained solution was applied to the release-treated surface of the PET film with an applicator so that the thickness after drying would be 75 μm. Next, the PET film to which the solution had been applied was heated and dried at 130°C for 10 minutes in an oven to obtain a curable film having a 75 μm-thick resin layer on the support film.
[0105] (4) Measurement of elastic modulus The curable resin composition applied in a sheet form using an applicator or the like was dried under conditions of 130°C for 10 minutes, and then heated at 300°C for 1 hour to obtain a film of the cured product of the curable resin composition having a thickness of 500 μm. The obtained film sample was punched out to a size of 5 mm x 35 mm to prepare a measurement sample. The obtained measurement sample was measured for its elastic modulus at 80°C using a dynamic viscoelasticity measuring device (manufactured by IT Measurement and Control Co., Ltd., DVA-200) under conditions of a constant temperature rise tensile mode, a temperature rise rate of 5°C / min, and a frequency of 1 Hz.
[0106] (5) Measurement of glass transition temperature of cured product The resin layer of the obtained curable film was heated at 300°C for 1 hour in the atmosphere to be thermally cured. The glass transition temperature of the obtained cured product was measured using a differential scanning calorimeter (220C, manufactured by Seiko Instruments Inc.) under a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min) in accordance with a method conforming to JIS K6240:2011 under the conditions of a measurement temperature of -100 to 200°C and a heating rate of 10°C / min.
[0107] (6) Manufacturing of Laminates The obtained curable film was vacuum laminated on an 8-inch silicon wafer having a step of 10 μm while heating the stage to 80° C. At this time, the vacuum degree was 100 Pa and the lamination pressure was 0.1 MPa. After lamination, before peeling off the backing film, the wafer was rolled twice again at a vacuum degree of 100 Pa and a lamination pressure of 0.1 MPa to remove air bubbles at the interface between the resin layer and the silicon wafer. The backing film was then peeled off, and the wafer was heated at 300° C. for 60 minutes to obtain a laminate (10 μm) having an organic layer with a thickness of 75 μm. Also, a laminate (50 μm) was obtained in the same manner, except that an 8-inch silicon wafer having a step of 50 μm was used.
[0108] (Examples 2 to 7, Comparative Examples 1 to 4) A curable film and a laminate were obtained and each measurement was performed in the same manner as in Example 1, except that the composition of the solution, the drying conditions of the solution, and the structure of the curable film were as shown in Table 1. The raw materials in the table are as follows. In addition, in Comparative Example 3, the viscosity was too low to form a film, and in Comparative Example 4, the solution was repelled within the support film during drying and only partially dried, so that the film was not formed. Therefore, "(6) Production of a laminate" was not performed, and the following evaluations were not performed. PGMEA: Propylene glycol monomethyl ether acetate
[0109] Comparative Example 5 (1) Preparation of solutions Cyclopentanone was added to 100 parts by weight of the obtained resin A, 1 part by weight of the obtained heat-resistant resin (resin E), and 0.1 part by weight of the catalyst so that the solid concentration was 65% by weight, and mixed to obtain a solution.
[0110] (2) Measurement of elastic modulus The curable resin composition applied in a sheet form using an applicator or the like was dried under conditions of 130°C for 10 minutes, and then heated at 300°C for 1 hour to obtain a film of the cured product of the curable resin composition having a thickness of 500 μm. The obtained film sample was punched out to a size of 5 mm x 35 mm to prepare a measurement sample. The obtained measurement sample was measured for its elastic modulus at 80°C using a dynamic viscoelasticity measuring device (manufactured by IT Measurement and Control Co., Ltd., DVA-200) under conditions of a constant temperature rise tensile mode, a temperature rise rate of 5°C / min, and a frequency of 1 Hz.
[0111] (3) Measurement of glass transition temperature of cured product The cured film obtained in the same manner as in "(2) Measurement of elastic modulus" was heated in air at 300°C for 1 hour to be thermally cured. The glass transition temperature of the obtained cured product was measured using a differential scanning calorimeter (220C, manufactured by Seiko Instruments Inc.) under a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min) at a measurement temperature of -100 to 200°C and a heating rate of 10°C / min according to a method conforming to JIS K6240:2011.
[0112] (4) Manufacturing of Laminates 10 g of the obtained solution was discharged onto the center of an 8-inch silicon wafer having a step of 10 μm. Next, spin coating was performed at a rotation speed of 500 rpm for 17 seconds using a spin coater (ACT-400II; manufactured by ACTIVE Corporation). Next, the silicon wafer after spin coating was dried for 10 minutes in an oven at 125° C., and then heat-treated at 300° C. for 1 hour to obtain a laminate (10 μm) having an organic layer with a thickness of 75 μm. Also, a laminate (50 μm) was obtained in the same manner, except that an 8-inch silicon wafer having a step of 50 μm was used.
[0113] Comparative Example 6 A laminate was obtained in the same manner as in Comparative Example 5, except that in the preparation of the solution, 30 parts by weight of a filler was further added and then mixed with the solvent. In addition, the elastic modulus was also measured.
[0114] <Evaluation> The laminates obtained in the examples and comparative examples were evaluated as follows, and the results are shown in Table 1.
[0115] (Evaluation of heat resistance) The obtained laminate was heated for 3 hours at 400° C. The organic layer of the laminate after heating was visually inspected, and the heat resistance was evaluated by assigning "good" to the case where the film was not cracked and "poor" to the case where the film was cracked.
[0116] (Boyd's evaluation) The organic layers of the resulting laminate were observed under an optical microscope to measure the degree to which voids (air gaps) occurred in the grooves of the wafer steps. The lamination voids were evaluated according to the following evaluation criteria. ◎: No voids ○: Voids are less than 10% of the groove area △: Voids are 10% to less than 30% of the groove area ×: Voids are 30% or more of the groove area
[0117] (Evaluation of dent amount) The grooves of the silicon wafer on the surface of the organic layer of the obtained laminate were observed using a laser microscope (OLS4100; manufactured by Olympus Corporation) and the amount of recession in the grooves of the organic layer was measured to evaluate the step filling ability.
[0118] [Table 1] [Industrial Applicability]
[0119] According to the present invention, it is possible to provide a method for producing a curable film that can form a uniform film on a support film, and the cured film has excellent heat resistance and can exhibit excellent step-filling performance even when used on a substrate having large irregularities, a curable film obtained by the method for producing a curable film, a laminate using the curable film, an imaging device and a semiconductor device having the laminate, and a method for producing the laminate. [Explanation of symbols]
[0120] 1 First Substrate 2 Chip 3 Organic layer 4 Inorganic layer 5 Support substrate 6 Second Board 7 Third Board 8 electrodes 9 Fourth Board 10 Through hole 11 Barrier metal layer
Claims
1. A step of preparing a solution by dissolving a curable resin composition containing a silsesquioxane represented by the following structural formula (1) in a solvent having a boiling point of T° C. so as to have a viscosity of 700 mPa·s or more and 2000 mPa·s or less; applying the solution onto a release-treated surface of a support film that has been subjected to a release treatment so that the thickness after drying is 50 μm or more; and drying the applied solution at a temperature of T+50° C. or higher for 10 minutes or longer. 【Chemistry 1】 In structural formula (1), R 0 , R 1 and R 2 each independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. Each of m and n represents an integer of 1 or more.
2. The method for producing a curable film according to claim 1, wherein the solution has a solids concentration of 50% by weight or more.
3. The method for producing a curable film according to claim 1 or 2, wherein the boiling point of the solvent is less than 100°C.
4. The method for producing a curable film according to claim 1 or 2, wherein the support film comprises polyethylene terephthalate.
5. A curable film having a support film that has been subjected to a release treatment and a resin layer laminated on the release-treated surface of the support film, wherein the resin layer contains a silsesquioxane represented by the following structural formula (1), and the thickness of the resin layer is 50 μm or more. 【Chemistry 2】 In structural formula (1), R 0 , R 1 and R 2 each independently represents a linear, branched or cyclic aliphatic group, an aromatic group, or hydrogen. The aliphatic group and the aromatic group may or may not have a substituent. Each of m and n represents an integer of 1 or more.
6. The curable film according to claim 5 , wherein the relationship tr>tf is satisfied, where tr is the thickness of the resin layer and tf is the thickness of the support film.
7. 7. The curable film of claim 5 or 6, wherein the support film comprises polyethylene terephthalate.
8. The curable film according to claim 5 or 6, wherein the resin layer is heated at 300°C for 1 hour in the atmosphere and cured, and the cured product has a glass transition temperature of 25°C or higher and 100°C or lower.
9. A laminate comprising a substrate having a first surface having projections and recesses and a second surface opposite the first surface, the substrate having an organic layer formed on the first surface and comprising a cured resin layer of the curable film according to claim 5 or 6.
10. 10. The laminate according to claim 9, wherein the height of the projections and recesses of the substrate is 30 μm or more.
11. An imaging device comprising the laminate according to claim 9.
12. A semiconductor device comprising the laminate according to claim 9.
13. The stack of claim 9 , wherein the substrate is a first substrate having a plurality of chips on a first surface thereof.
14. 14. The laminate of claim 13, wherein the first substrate of the organic layer has an inorganic layer on the side not laminated.
15. The laminate according to claim 14 , further comprising a supporting substrate on the surface of the inorganic layer on which the organic layer is not laminated.
16. The laminate according to claim 13 , further comprising a second substrate on the second surface side of the first substrate, the first substrate and the second substrate being electrically connected to each other.
17. A laminate having an organic layer made of a cured product of the resin layer of the curable film according to claim 5 or 6 between a third substrate having an electrode and a fourth substrate having an electrode, a laminate, wherein the electrode of the third substrate and the electrode of the fourth substrate are electrically connected via a through hole penetrating the organic layer.
18. 20. The laminate of claim 17, further comprising an inorganic layer between the third substrate and the fourth substrate.
19. The laminate according to claim 17 , further comprising a barrier metal layer on the surface of the through hole.
20. A step of heating the curable film according to claim 5 or 6 to a temperature equal to or higher than the glass transition temperature of the resin layer, and laminating the resin layer on a first surface of a substrate having a first surface having projections and recesses and a second surface opposite the first surface; peeling the support film from the curable film after lamination; and heating the substrate on which the resin layer is laminated to form an organic layer made of a cured product of the resin layer on the substrate.
21. A step of heating the curable film according to claim 5 or 6 to a temperature equal to or higher than the glass transition temperature of a resin layer, and laminating the resin layer onto a surface of a third substrate having an electrode and a fourth substrate having an electrode, the surface having the electrode; peeling the support film from the curable film after lamination; a step of heating the third substrate and the fourth substrate on which the resin layer is laminated to form an organic layer made of a cured product of the resin layer on the third substrate and the fourth substrate; forming a through hole in each of the organic layers; filling each of the through holes with a conductive material; a step of polishing the surfaces of the third substrate and the fourth substrate on the side where the conductive material is filled to form bonding electrodes; a step of bonding the third substrate and the fourth substrate together so that the bonding electrodes of the third substrate and the fourth substrate are bonded to each other.
Citation Information
Patent Citations
Image sensor in which light receiving region is extended and method of manufacturing the same
JP2006191081A
Cited By
Resin material, resin film, laminated film, and multilayer printed wiring board
WO2026070829A1